Acesülfam-Metil Piridin Geçiş Metal Komplekslerinin Sentezi, Yapısı, Spektroskopik, Termik ve Kromik Özellikleri - Adıyaman, Elif (Ondokuz Mayıs Üniversitesi, Fen Bilimleri Enstitüsü, 2005)
Bu çal mada piridin, 3-metil piridin, 4-metil piridin ve 2-amino-3-metil piridinligant içeren kar k ligantl metal-acesülfam kompleksleri sentezlenerek, bukomplekslerin yap ve özellikleri elementel analiz ve manyetik ölçümler, UV-Vis. veFT-IR spektroskopisi, e zamanl termik analiz teknikleri (TG, DTG ve DTA), kütlespektroskopisi ve x- nlar tek kristal k r n m yöntemi ile incelendi.Sentezlenen acesülfam-piridin ve acesülfam-metil piridin komplekslerininmanyetik duyarl l k ölçümlerinden manyetik momentleri hesapland ve komplekslerinyüksek spin ve dü ük alan kompleksleri oldu?u tespit edildi.Bu komplekslerdeki ligantlar n ba?lanma ekillerinin anla lmas için[Cu(acs)2(3-pic)2] ve [Ni(acs)2(3-pic)2(H2O)2] komplekslerinin kristal yap larincelenerek moleküler yap s ayd nlat ld . [Cu(acs)2(3-pic)2] kompleksinde nötral ligant(3-metil piridin) Cu(II) iyonuna halka azot üzerinden ba?lan rken, acesülfamato ligantkarbonil oksijeni ve imin azotu üzerinden koordine olarak çift di li davranmaktad r.[Ni(acs)2(3-pic)2(H2O)2] kompleksinde, [Cu(acs)2(3-pic)2] kompleksinden farkl olarakacesülfamato ligant tek di li davranarak Ni(II) iyonuna karbonil oksijeni üzerindenba?lanmaktad r. Acesülfamat anyonu çok di li ligant olarak, farkl metal iyonlar na N,Oco, Ooso veya O atomlar üzerinden koordine olabilir, bu nedenle [Cu(acs)2(3-pic)2] ve[Ni(acs)2(3-pic)2(H2O)2] komplekslerinin FT-IR spektrumlar ile di?er komplekslerinFT-IR spektrumlar kar la t r larak acesülfamato ligant n n ba?lanma ekilleribelirlendi.Komplekslerin termik özellikleri kütle spektroskopisi ve e zamanl TG, DTG veDTA teknikleri ile incelendi. Yap s nda kristal su ve akua ligant bulunan komplekslerinilk bozunma a amas n n dehidrasyon veya deakuasyon oldu?u, ikinci bozunmaa amas nda ise nötral ligant n uzakla t ? ve takiben acesülfamato ligantlar n n SO2çk ile bozundu?u tespit edildi.Komplekslerin kromotropik özellikleri termik ve spektroskopik yöntemler ileincelendi. Sentezlenen komplekslerin s cakl k, çözücü ve iyon etkisi ile termokromizm,solvatokromizm ve iyonokromizm özelli?i gösterdi?i belirlendi. Komplekslerin yap salözellikleri ile kromik özellikleri aras ndaki ili ki incelendi.Anahtar Kelimeler: Acesülfamat metal kompleksleri, Metil piridin, Termik analiz, X-nlar , Kromizm

In this work, mixed-ligand complexes of pyridine, 3-methyl pyridine, 4-methylpyridine and 2-amino-3-methyl pyridine with metal-acesulfamato were synthesized andtheir strustures and properties were investigated by elemental analyses, magneticmeasurements, UV-Vis, FT-IR spectroscopic, simultaneous thermal analysis techniques(TG, DTG and DTA) , mass spectroscopic and single crystal X-ray diffraction method.The spin only magnetic moments have been calculated from the magneticsusceptibility measurement of the complexes. The magnetic moments showed that allthe complexes were high spin type.The crystal structures of [Cu(acs)2(3-pic)2] and [Ni(acs)2(3-pic)2(H2O)2]complexes have also been studied to understand bonding of the ligands in thesecomplexes. Their structures were identified by X-ray single crystal difraction method.In [Cu(acs)2(3-pic)2] complex neutral ligand (3-methyl pyridine) acts as a monodentateN- donor, acesulfamato ligand (acs) acts as a bidentate N,O-donor. The difference of[Ni(acs)2(3-pic)2(H2O)2] from [Cu(acs)2(3-pic)2] is that acesülfamato ligand acts as amonodentate O-donor ligand in the Ni(II) complexe. The acesulfamate anion,C4H4NO4S(acs), has several potential donor atoms and thus, as a polyfunctional ligand, it canengage in N, OCO, OOSO or O coordination with different so that, the FT-IR spectras of[Ni(acs)2(3-pic)2(H2O)2] and [Cu(acs)2(3-pic)2] complexes compare with the FT-IRspectra of the other complexes to understand the bonding of acesulfamato ligand inthese complexes.The thermal behaviour of these complexes were investigated by massspectroscopic and means of TG, DTG and DTA techniques. In the thermal analysis ofthe complexes with aqua ligand or crystal water, the first decomposition stagecorrespond to the dehydration or deaquation. In the second stage correspond to releaseof neutral ligand. In third step acesulfamate ligand decomposes SO2 likely to beproduced.The chromotropic properties of all complexes have been studied using termaland spectral analysis. Thermochromism is a colour change brought about by heat,solvatochromism by solvents and ionochromism by ions. Acesulfamao-methyl pyridinecomplexes exhibit thermochromism, solvatochromism and ionochromism. Therelationship between the chromotropic properties and structure of complexes wasinvestigated.Keywords: Acesulfamate metal complexes, Methylpyridine, Thermal analysis, X-ray,Chromism.
Synthesis, Structure, Spectroscopic, Thermal and Chromic Properties of Acesulfame-methyl Pyridine Transition Metal Complexes
Tez (yüksek lisans) -- Ondokuz Mayıs Üniversitesi, 2005
Libra Kayıt No: 17026
Keywords: Chemistry; Kimya; TEZ YÜK LİS A235a 2005